Storytelling and training to advance individual recovery skills (STAIRS). A feasibility study of a blended program to support personal recovery among patients with a major depressive disorder in remission - Wedema, David; Siero, Joanieke; Korevaar, Eliza L.; Wardenaar, Klaas J.; Alma, Manna A.; Schoevers, Robert A. (Frontiers in Psychiatry, 2022)
Because major depressive disorder (MDD) has a strong negative impact on patients’ lives, well designed treatment programs are needed that address the lasting effects of MDD. Previous work has shown that such programs should not only focus on symptomatic recovery, but also on the subsequent personal recovery process. Currently, few programs with this specific focus exist. Therefore, this study aimed to assess the feasibility of a newly developed blended program to support the personal recovery process of MDD patients: Storytelling and Training to Advance Individual Recovery Skills (STAIRS). STAIRS is a program using peer support and guidance by experts by experience and clinicians, which can be added to regular depression treatment when symptomatic recovery is almost reached. Topics addressed in this program are: 1) effects of depression and treatment; 2) structure; 3) (self) stigma; 4) self-image; 5) meaning of life; 6) connection to others; 7) physical health; 8) relaxation; and 9) preventing relapse. Experiences with the STAIRS program were collected from five participating patients with questionnaires and a focus-group interview, as well as from four trainers using semi-structured interviews. Participants valued the topics addressed in STAIRS, the used working methods, the presence of an expert by experience and the ability to share experiences with peers. The use of an online platform and the involvement of others is seen as potentially supportive but turned out to be more challenging. Perceived effects of STAIRS include positive changes in participants’ daily lives and their contacts with others. Overall, the results indicate that when implemented accessibly, STAIRS is a promising and feasible program to foster personal recovery among patients recovering from MDD.